Sustainability of European agricultural holdings - Dos-Santos, M. J. P. L.; Ahmad, N. (Journal of the Saudi Society of Agricultural Sciences, 2020)
European agricultural activity has an important contribution to European and global food security and also in the preservation of countryside and livelihood. The main goal of this paper is to analyze the agricultural sustainability of the twenty-eight Member States of the European Union in order to promote sustainable agriculture, food security and rural development in the European region. Information and data used are obtained from the European Commission database. The methodology includes the min–max approach and multivariate techniques, namely, Cluster and Factorial Analysis. The findings show the existence of three different clusters of farms in European countries, namely, Central European countries, New Eastern Member States, and the Mediterranean countries. The results also conclude that European agriculture and their respective farms have moderate sustainability where the subsidies from Common Agricultural Policy have a positive impact on. Moreover, agricultural activity in the European Central countries presents the highest value in economic contribution, whereas the Mediterranean countries present more contribution in environmental terms. The highest contribution in terms of creating rural jobs is found in Eastern countries. The main conclusion highlights the need to better adjust agricultural policies among the European Member States in order to better promote the sustainability of agriculture in Europe.